Home financing through the Musharakah Mutanaqisah contracts: Some practical issues - Meera, Ahamed Kameel Mydin; Abdul Razak, Dzuljastri (King Abdulaziz University, 2009)
Meera and Abdul Razak (2005) compared the al-Bay’ Bithaman Ajil (BBA) and the Musharakah Mutanaqisah Partnership (MMP) contracts. The BBA, a murabahah contract, was argued to be problematic and even unIslamic for long-duration contracts. The MMP contract which is a combination of musharakah (partnership) and ijarah (rental) contracts was argued to be a more appealing alternative. In the MMP, the equity of the financier diminishes progressively while, in accordance, the equity of the customer grows. Unlike for the BBA contract, scholars are consensus on the Shari’ah permissibility of the MMP contract. A mathematical derivation for the MMP showed that the formula for the MMP to be similar to the formula used in conventional loans but nonetheless with the interest rate replaced with the rental rate. Therefore, one major advantage of MMP was argued to be that it can avoid interest (riba) totally. Also, unlike under the BBA, the balance of financing, at any point in time, never exceeds the original price of the asset. Nevertheless, some practical issues need to be addressed particularly the means of estimating the rental rate, tax issues, defaults and asset value appreciation. This paper discusses these issues. When not profitable for the banks when rentals rates fall short of interest rates, the MMP can be implemented through cooperatives, which can be also an investment avenue for members.